Off-ball movement in football: Evidence on the relationship between team strength, performance, success and runs in behind - Thönnessen, T.; Memmert, D.; Mews, D.; Wunderlich, F. (International Journal of Performance Analysis in Sport, 2025)
Running performance is a key element of football, but results of its relation to success have been inconclusive so far. Considering runs with a clear tactical intent instead of analysing aggregate running performance could be a promising approach to overcome this problem. Thus, the present study analyses more than 4600 so-called runs in behind from 54 matches of the 2018/19 season of the German first division (Bundesliga). Regression analysis was used to evaluate whether runs in behind possess a relationship to success, team strength and performance in football. While finding a significant relationship between the total number of runs in behind per match and success, performance and goals, this effect fully disappears after normalising for ball possession. However, if only considering contextualised runs in behind, a significant relationship with performance, team strength and goals (runs into a critical area: p*<*0.001 or accompanied by a forward pass: p*<*0.05) is found even if normalising for ball possession. Therefore, contextualised runs in behind can be considered a relevant factor in explaining and understanding success-enhancing strategies in football. Moreover, this study provides evidence that it is crucial to standardly consider important contextual variables (e.g. ball possession) in performance analysis.